The Effectiveness Of Criminal Eradication On Hoax Information And Fake News - Hernawan Dewatana; Siti Ummu Adillah (Law Development Journal, 2021)
The rise of hoax informations/ fake news circulating can have a negative impact on the development of the Indonesian state. Hoaxes can cause debates to the point where it is not impossible to break friendships. Moreover, the hoax that contains SARA which is very vulnerable to invite friction between communities, disturbs the stability of the country and diversity. This study aims to determine the effectiveness of law enforcement in cases of spreading false information. The research method is sociological juridical. The basic regulations for the spread of fake news or hoaxes have been regulated in Act No. 11 of 2008 which has been changed to Act No. 19 of 2016 articles 28 paragraphs 1 and 2. It can be charged with other related articles, namely articles 310, 311, 378 and 390 of the Criminal Code. With the rapid development of today's technology, the more diverse and many new crimes committed through electronic media, in this case the spread of fake news (Hoax) which is currently rife. The current regulations related to fake news have regulated not only the creators of the fake news who are given criminal sanctions but also for the perpetrators who participate in sharing (forwarding) the fake news.